Care willingness and demand of residents under 60 years of age in western China: a cross-sectional study - Li Zhao; Feng Ying Zhang; Li nan Cheng; Xiao feng Xie; Xiu ying Hu; Xiao yang Dong (BMJ Open)
Objectives The objective was to examine care willingness and demand of residents under 60 years of age after retirement.Setting The staged cluster sampling method was used between August and October 2018 in Dujiangyan, Sichuan Province, China.Participants 2282 participants under 60 years of age were surveyed in 2018 by the staged cluster sampling method in China.Primary and secondary outcome measures The results of care willingness and demand were assessed by multiple comparisons of χ2 test and multivariable logistic regression.Results The respondents who preferred institution-based care, home-based care and community-based care accounted for 39.5%, 38.3% and 20.2% respectively, whereas only 2.1% preferred home-based self-care. The main reasons for the respondents to choose institution-based care included better medical care (31.9%), better daily care (27.0%), burden reduction for children (26.3%), better accommodation (22.8%), satisfied living environment (21.6%) and low consumption (12.3%). The factors that affected care willingness and demand included age, ethnicity, educational attainment, marital status, occupation and the current type of residence.Conclusions The results revealed the care willingness and demand of residents under 60 years of age after retirement and relevant decision factors. This study provides a certain theoretical and practical significance for the development of the care willingness mode and promotes the cognition of policy-makers and researchers, and also provides the basis for decision-making.